2016
DOI: 10.1016/s2213-8587(16)30009-2
|View full text |Cite
|
Sign up to set email alerts
|

Long-term effects of neighbourhood deprivation on diabetes risk: quasi-experimental evidence from a refugee dispersal policy in Sweden

Abstract: SUMMARY Background While numerous studies have shown associations between neighborhood quality and chronic disease outcomes, such correlations are potentially confounded by selection of different types of people into different neighborhood environments. We sought to identify the causal effects of neighborhood deprivation on type 2 diabetes risk, by comparing refugees to Sweden who were actively dispersed by government policy to low-, moderate-, or high-deprivation neighborhoods. Methods We studied national … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
107
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 98 publications
(121 citation statements)
references
References 31 publications
13
107
0
1
Order By: Relevance
“…Another study from Sweden created a historical cohort to test the hypothesis that neighbourhood deprivation affects the development of type 2 diabetes among refugees quasi-randomly assigned to neighbourhoods throughout the country 26. The study provides evidence that exposure to high neighbourhood deprivation (compared with low deprivation) increases the risk for diabetes26 an association that has also been found in Germany among the general population 14 27…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Another study from Sweden created a historical cohort to test the hypothesis that neighbourhood deprivation affects the development of type 2 diabetes among refugees quasi-randomly assigned to neighbourhoods throughout the country 26. The study provides evidence that exposure to high neighbourhood deprivation (compared with low deprivation) increases the risk for diabetes26 an association that has also been found in Germany among the general population 14 27…”
Section: Discussionmentioning
confidence: 96%
“…One of these has assessed the association between neighbourhood income inequality (based on the Gini coefficient) and the risk of being admitted to hospitals among refugees in Sweden and found no statistically significant effect of the exposure on the outcome 25. Another study from Sweden created a historical cohort to test the hypothesis that neighbourhood deprivation affects the development of type 2 diabetes among refugees quasi-randomly assigned to neighbourhoods throughout the country 26. The study provides evidence that exposure to high neighbourhood deprivation (compared with low deprivation) increases the risk for diabetes26 an association that has also been found in Germany among the general population 14 27…”
Section: Discussionmentioning
confidence: 99%
“…Studies from many parts of the world have since shown that the prevalence of diabetes is high in migrants . Migration involves losses, disruption to usual life habits, exposure to new experiences and challenges that can impact adiposity and T2D through nutrition transition to high‐caloric diets, physical inactivity, stress and neighbourhood deprivation . Pacific people (40%), Māori (27%) and Asian (20%) people are more likely to reside in the poorest areas (NZ Dep 13 Quintile 5 areas) than people of European descent .…”
Section: Discussionmentioning
confidence: 99%
“…Pacific people (40%), Māori (27%) and Asian (20%) people are more likely to reside in the poorest areas (NZ Dep 13 Quintile 5 areas) than people of European descent . Several studies have shown a strong association between disadvantaged neighbourhood environments and the increased risk of developing T2D . The potential mediating factors include reduced employment and income opportunities, the purchase of calorie‐dense food, limited psychosocial resources, language barriers and poor coping strategies resulting in chronic high stress …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation